P213 Real-world effectiveness of benralizumab in patients with eosinophilic granulomatosis with polyangiitis (EGPA). (11th November 2022) - Alam, V; Agarwal, S; Hopkins, C; D'cruz, D; Fernando, MMA; Ismail, TF; Dhariwal, J; Nanzer, AM; Jackson, DJ
Abstract : Introduction: Eosinophilic granulomatosis with polyangiitis (EGPA) is a multi-system disorder characterised by asthma, eosinophilia, and vasculitis. Treatment options include oral corticosteroids (OCS) and other immunosuppressants. Recently, the anti-IL5 biologic mepolizumab has demonstrated efficacy in a phase 3 study. 1 However, the anti-IL5R biologic benralizumab offers more complete tissue eosinophil depletion and is therefore of considerable interest. Here we report the real-world effectiveness of benralizumab treatment in patients with EGPA. Methods: We retrospectively analysed patients with EGPA who had completed at least 24 weeks treatment with benralizumab in our tertiary multidisciplinary EGPA clinic. All patients had severe eosinophilic asthma (SEA) and met NICE eligibility criteria for benralizumab under this. Clinical data were collected at baseline and over the first year of treatment. Remission was defined as a Birmingham Vasculitis Activity Score of 0 and receipt of OCS ≤4 mg/day or for adrenal insufficiency. An EGPA relapse was defined as either: evidence of new vasculitis-related symptoms excluding asthma exacerbations (AE), or including AE. Results: Fifty-nine patients were included: 8 completed 24 weeks of treatment with 51 completing 48 weeks. 14/59 (24%) were ANCA positive. 49/59 (83%) were taking OCS at baseline with a median (range) daily dose 10.0 mg (2–40). At 24 weeks, 61% of patients had stopped their OCS for EGPA and SEA. This increased to 74% by 48 weeks. In total, remission status was achieved in 33/51 (64.7%) of patients at 48 weeks with no significant differences based on ANCA status. At 48 weeks, 47/51 (92.2%) remained relapse-free excluding AE in the definition. This dropped to 32/51 (62.7%) if AE were included, with a significant difference according to ANCA status for the latter classification only (p=0.036), figure 1 . Conclusion: In the largest case series of patients with SEA and co-morbid EGPA treated with benralizumab to date, we observed a significant steroid-sparing effect with almost two-thirds of patients achieving remission by 48 weeks. Pulmonary relapses appeared more common in ANCA-positive patients suggesting non-eosinophil mediated inflammation may be more important in this phenotype. References: Wechsler, M.E., et al . Mepolizumab or Placebo for Eosinophilic Granulomatosis with Polyangiitis. N Engl J Med, 2017; 376 (20): p. 1921–1932.